Cyanobacteria as Candidates to Support Mars Colonization: Growth and Biofertilization Potential Using Mars Regolith as a Resource - Macário, Inês P. E.; Veloso, Telma; Frankenbach, Silja; Serôdio, João; Passos, Helena; Sousa, Clara; Gonçalves, Fernando J. M.; Ventura, Sónia P. M.; Pereira, Joana L. (Frontiers in Microbiology, 2022)
Cyanobacteria are indicated as organisms that can possibly support Mars colonization, contributing to the production of oxygen and other commodities therein. In this general context, the aim of this work was to evaluate the ability of three species of cyanobacteria (Anabaena cylindrica, Nostoc muscorum, and Arthrospira platensis) and a green microalga (Chlorella vulgaris) to grow using only the resources existing in Mars, i.e., water and Martian regolith stimulant (MGS-1), under an Earth-like atmosphere. A Martian regolith extract was produced and used as a culture medium to grow these species. Their growth was assessed during a period of 25 days, using optical density and fluorometric parameters. After this period, the possible contribution of end-of-life cyanobacteria/microalga as biofertilizing agents was also assessed, using the macrophyte Lemna minor as a vegetable model. Among the three species, N. muscorum showed the best growth performance when compared to the other species, while A. platensis and C. vulgaris were not able to thrive on Mars regolith extract. Therefore, N. muscorum should be the target of future studies not only due to their role in oxygen production but also due to their possible use as a food source, as many members of the Nostoc genus. Cyanobacteria and microalgae (A. platensis and C. vulgaris) showed good abilities as biofertilizing agents, i.e., they stimulated biomass (i.e., dry weight) production at levels comparable to the plants that grew on standard synthetic medium. The highest yield was reached with A. platensis, while the lowest was achieved using the media with N. muscorum. FTIR-ATR (Fourier transform infrared with attenuated total reflectance) spectroscopy showed that the differences between the plants grown on media with or without Martian regolith seem to be related mainly to polysaccharides.